Evaluation Study of SC/ST Welfare Programs of Mandya District: Assessing the Impact of SC/ST Welfare Programs in Mandya District, India (Journal of Advances and Scholarly Researches in Allied Education, 2018)
To a nation to turn into a created country equivalent development everything being equal citizens is basic. On the off chance that any social gathering stays in reverse in any nation, that nation can't be proclaimed as a created country. The division, for example, social welfare is made to advance the financial development of the individuals who have remained in reverse. Because of chronicled reasons the SC's and ST's have stayed in reverse altogether fronts of life. Henceforth social welfare division has been made to deal with the interests of the SC's and ST's in India. In this study, welfare programs of SCST of Mandya district have been evaluated.